2018
DOI: 10.3389/fnmol.2018.00227
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Function of Connexin 32 in the Peripheral Nervous System?

Abstract: Connexin 32 (Cx32) is a fundamental protein in the peripheral nervous system (PNS) as its mutations cause the X-linked form of Charcot–Marie–Tooth disease (CMT1X), the second most common form of hereditary motor and sensory neuropathy and a demyelinating disease for which there is no effective therapy. Since mutations of the GJB1 gene encoding Cx32 were first reported in 1993, over 450 different mutations associated with CMT1X including missense, frameshift, deletion and non-sense ones have been identified. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 105 publications
(161 reference statements)
0
41
0
Order By: Relevance
“…Many Cx32 mutants were proven to affect trafficking when expressed by transfection in mammalian cell lines (21). Other recent studies also identified dysfunction in specific permeability of important molecules with molecular masses of more than 1 kDa (7,24). These might be the two main explanations of PNS involvement in CMTX1 patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many Cx32 mutants were proven to affect trafficking when expressed by transfection in mammalian cell lines (21). Other recent studies also identified dysfunction in specific permeability of important molecules with molecular masses of more than 1 kDa (7,24). These might be the two main explanations of PNS involvement in CMTX1 patients.…”
Section: Discussionmentioning
confidence: 95%
“…In myelinating Schwann cells, Cx32 localizes at the paranodes of non-compact myelin, providing a channel for the exchange of ions, and small molecules across the myelin sheath. The diverse functions of Cx32 include the transduction of electrical signals, growth control, and cell differentiation (7). The pathogenic mechanisms by which different GJB1 mutations cause CMTX1 are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Altered epidermal lipid processing and Ca 2+ distribution were reported also in Cx26 S17F/+ mice, another model for KID syndrome [73] , and we have shown previously that abEC1.1 is effective in vitro against at least two KID variants of Cx26 [35] . In addition, at least three Cx32 mutations (S85C, D178Y, F235C) causing Charcot-Marie-Tooth disease, X-linked dominant 1 (CMT1X, OMIM # 302800 ), a demyelinating peripheral neuropathy, produce hemichannels with augmented activity [4] and, possibly, deregulated ATP release [74] . Few therapeutic antibodies address dermatological conditions [ 49 , 75 , 76 ] or neurodegeneration [77] .…”
Section: Discussionmentioning
confidence: 99%
“…Cx32 has multifaceted functions described in glial cells in the CNS (Abrams, 2017) and PNS (Bortolozzi, 2018). Recent evidence indicated the expression of functional Cx32 HCs that release ATP during electrical stimulation on mice sciatic nerves, which from cultured SCs, by depolarization evoked through a high extracellular potassium concentration (Nualart-Marti et al, 2013).…”
Section: Gap Junction Channels In Myelinating Schwann Cellsmentioning
confidence: 99%
“…Most GJB1 mutations cause disability through the loss of function of Cx32 (Bruzzone et al, 1994; Kleopa et al, 2012). In particular, Cx32 mutations related to CMTX1 could be organized into five classes: (1) Cx32 protein is not synthesized; (2) mutant Cx32 protein has a reduced expression (with a normal transcription), (3) mutant Cx32 protein has a normal expression but is not transported to the plasma membrane; (4) mutant Cx32 protein forms HCs but not functional GJCs; and (5) mutant Cx32 protein forms GJCs and HCs with altered electrical, gating or permeability properties (Bortolozzi, 2018).…”
Section: Diseases Associated With Dysfunction Of Connexins In Schwannmentioning
confidence: 99%